Implementation of mobile attendance application using geo-fence technique - Mokhairi, Makhtar; Engku Fadzli Hasan, Syed Abdullah; Azrul Amri, Jamal (Asian Research Publishing Network, 2016)
RACT Attendance systems were developed before the mobile device has been introduced to the market. The traditional system and web-based system are accepted method to keep track the attendance of the staff. Some companies introduce a secure and expensive system such as RFID and Thumbprint technology. With the emergence of the GPS enabled device in smart phone, there is a need to introduce a smart phone as a medium to clock in and clock out for staff attendance, especially who work off-site. This paper will discuss the geo-fence technique and its implementation for mobile attendance android based application. The technique is suitable for analysing the location and boundaries of a GPS mobile enabled especially for staffs who are working away from the office or outstation. From the implementation conducted, the application functions well to keep track staff attendance records.